The Influence of School Structure, Assets, and Facilities on the Learning Motivation of Eighth-Grade Students at SMP Negeri 3 Tebing Tinggi - Afni Maulani Octavia Siagiaan (Yayasan Bayt Shufiya Nusantara, 2023)
This study aims to determine the influence of school facilities and infrastructure on the learning motivation of grade VIII students of SMP Negeri 3 Tebing Tinggi. The method used is a quantitative method with a population of 100 students. Data collection was carried out through the distribution of questionnaires, and data analysis was carried out using the SPSS program. The results showed that the variable structure of infrastructure facilities had a significant effect on students' learning motivation with a t-calculation value of 7,707 > t-table of 1,660 and a significance value of 0.000 < 0.05. The magnitude of the influence of these variables on learning motivation was 61.4%, while the remaining 38.6% was influenced by other factors outside of this study. These findings indicate that the quality of governance and the availability of school facilities play an important role in increasing students' motivation to learn.